Responses to N Deficiency in Stay Green and Non-Stay Green Argentinean Hybrids of Maize - Antonietta, Mariana; Acciaresi, Horacio Abel; Guiamet, Juan José (2017)
Breeding has developed better yielding maize hybrids for low N environments, which also have delayed leaf senescence (‘stay green’ trait, SG). Here, we studied whether the SG trait can further improve yield of modern hybrids under N-limiting conditions. In two field experiments, four maize hybrids with different senescence behaviour were grown under three N fertilization levels, from 0 to 200 kg N ha 1 (N0, N100 and N200). After silking, hybrids differed for senescence depending on the canopy layer (P < 0.05): the SG AX878 only delayed senescence at the mid and upper canopy layers while the SG NK880 delayed senescence of all layers. Across N doses, higher yields were achieved by both SG hybrids, AX878 and NK880 (P < 0.05) but yield was not only determined by senescence behaviour. Kernel weight (KW) response to N availability was larger for SGs than for their non-‘stay green’ counterparts. Delayed senescence in SG hybrids was not related to higher post-silking N uptake but to higher (P < 0.05) %N in leaves and lower (P < 0.05) %N in kernels at harvest (below the critical 1.1 % under N deficiency). Across N levels, KW positively related to N content per kernel, with a steeper slope (P < 0.05) for the SG hybrids. Taken together, our results suggest that a condition where N limits kernel growth, in a scenario of saturating C availability, may be common to stay green genotypes of maize.